The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1542/peds.2004-2626
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Differences in Parent Preference to Be Present for Painful Medical Procedures

Abstract: ABSTRACT. Objective. To examine ethnic differences between white, black, and Hispanic (Englishspeaking and Spanish-speaking) parents in their desire to remain present during their children's painful medical procedures.Methods. A convenience sample of parents from each of 4 ethnic groups (black, white, and Hispanic [divided into English-speaking Hispanic and Spanish-speaking Hispanic]) was surveyed regarding their preferences for remaining present for 5 hypothetical painful procedures: venipuncture, laceration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 19 publications
0
28
0
4
Order By: Relevance
“…[462][463][464][465][466][467][468][469][470][471] Studies show that family members who are present at a resuscitation would recommend it to others. 462,463,465,471,472 Parents of chronically ill children are comfortable with medical equipment and emergency procedures, but even family members with no medical background who were at the side of a loved one to say goodbye during the final moments of life believe that their presence was beneficial to the patient, [462][463][464]466,[471][472][473][474][475][476] comforting for them, 462-465,468 -471,476 and helpful in their adjustment [463][464][465]472,473,476,477 and grieving process. 477 Standardized psychological examinations suggest that, compared with those not present, family members present during attempted resuscitations have less anxiety and depression and more constructive grieving behavior.…”
Section: Family Presence During Resuscitationmentioning
confidence: 99%
“…[462][463][464][465][466][467][468][469][470][471] Studies show that family members who are present at a resuscitation would recommend it to others. 462,463,465,471,472 Parents of chronically ill children are comfortable with medical equipment and emergency procedures, but even family members with no medical background who were at the side of a loved one to say goodbye during the final moments of life believe that their presence was beneficial to the patient, [462][463][464]466,[471][472][473][474][475][476] comforting for them, 462-465,468 -471,476 and helpful in their adjustment [463][464][465]472,473,476,477 and grieving process. 477 Standardized psychological examinations suggest that, compared with those not present, family members present during attempted resuscitations have less anxiety and depression and more constructive grieving behavior.…”
Section: Family Presence During Resuscitationmentioning
confidence: 99%
“…61 Most parents surveyed indicated that they wanted to be offered the option of being present during the resuscitative effort for their child. 60,[71][72][73][74][75][76][77][78][79] In the absence of data documenting harm and in light of data suggesting that it may be helpful, offering select family members the opportunity to be present during a resuscitation is reasonable and desirable (assuming that the patient, if an adult, has not raised a prior objection) (Class IIa, LOE C for adults and Class I, LOE B for pediatric patients). Parents and other family members seldom ask if they can be present unless they are encouraged to do so by healthcare providers.…”
Section: Providing Emotional Support To the Family Providing Emotionamentioning
confidence: 99%
“…It is clear that cultural differences can contribute to how an individual or family manifests behavioral distress and anxiety [16][17][18][19] ; however, no predictable patterns have emerged with regard to a consistent pain experience within ethnic groups. 20 Studies have noted that Hispanic and black individuals with long-bone fractures were less likely to receive analgesics than were non-Hispanic white individuals. [21][22][23] A review of the National Hospital Ambulatory Medical Care Survey from 1992 to 1997 demonstrated that among patients with fractures, black children covered by Medicaid were least likely to receive parenteral sedation and analgesia.…”
mentioning
confidence: 99%